Efforts to Resolve Online Gambling Crimes at the Barelang City Police Resort - Pantano, Tony; Tri Bawono, Bambang (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Cyber crime, especially online gambling, requires law enforcement efforts, both to prevent and eradicate, so that it does not become more widespread. Conceptually, law enforcement is an activity to harmonize the relationship of a value in good and manifested rules and is also an attitude of action as a series of final stage value descriptions, in order to create, maintain and defend peaceful social life. This study aims to determine the legal construction of handling online gambling crimes in the concept of legal certainty, and efforts to resolve online gambling crimes at the Barelang City Police Resort. The approach used in this study is normative and empirical juridical. Normative juridical research refers to laws and regulations using secondary data. While empirical research is field research using primary data. The results of this study can be concluded. The legal construction of handling online gambling crimes in the concept of legal certainty that law enforcement against online gambling that has been carried out by the Barelang Police Criminal Investigation Unit uses the instrument of Article 303 of the Criminal Code, Article 27 paragraph (2) in conjunction with Article 45 of the Electronic Information and Transactions Law. Efforts to resolve online gambling crimes at the Barelang City Police as Investigators in handling online gambling crimes in prosecuting online gambling crimes in the jurisdiction of the Barelang Police include: Application of the Criminal Code and Law Number 11 of 2008 concerning Information and Electronic Transactions in online gambling cases. Inhibiting factors or obstacles faced in enforcing the law on online gambling crimes in the jurisdiction of the Barelang Police include the lack of understanding and mastery of Investigators in the field of information technology, not balanced with the development of the abilities of online gambling perpetrators and the use of electronic evidence requires expert testimony that requires a budget to finance the expert's honorarium.